2018
DOI: 10.1159/000490470
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Physical Frailty Have Additive Effect on the Nutritional Status and Clinical Outcome of Chinese Peritoneal Dialysis

Abstract: Background/Aims: Frailty and depression both contribute to malnutrition and adverse clinical outcome of peritoneal dialysis (PD) patients. However, their interaction is incompletely defined. Methods: We studied 178 adult Chinese PD patients. Physical frailty was assessed by a validated in-house questionnaire; depressive symptoms was screened by the Geriatric Depression Scale; nutritional status was determined by subjective global assessment (SGA) and malnutrition inflammation score (MIS). All patients were fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 34 publications
(54 reference statements)
3
31
0
4
Order By: Relevance
“…In China, the majority of elderly patients suffering from depressive symptoms received no medical attention or treatment for these symptoms (Feng et al 2014); therefore, family caregivers play an important role in ensuring the mental health and wellbeing of patients by providing them with comfort and support. Meanwhile, elderly people on PD with depressive symptoms may display additional symptoms, such as cognitive impairment, sleep disturbance and frailty (Dong et al 2016; Szeto et al 2018), which could place further demands on caregivers. In addition, depressive symptoms in patients have been associated with their non‐adherence to dietary and medication regimes, particularly among the dialysis population (Khalil & Frazier 2010; Alosaimi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In China, the majority of elderly patients suffering from depressive symptoms received no medical attention or treatment for these symptoms (Feng et al 2014); therefore, family caregivers play an important role in ensuring the mental health and wellbeing of patients by providing them with comfort and support. Meanwhile, elderly people on PD with depressive symptoms may display additional symptoms, such as cognitive impairment, sleep disturbance and frailty (Dong et al 2016; Szeto et al 2018), which could place further demands on caregivers. In addition, depressive symptoms in patients have been associated with their non‐adherence to dietary and medication regimes, particularly among the dialysis population (Khalil & Frazier 2010; Alosaimi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Iyasere et al [12] showed that patients on assisted PD had a higher prevalence of possible depression and higher Hospital Anxiety and Depression Scale (HADS) depression score than in-center hemodialysis patients, but their frailty scores were similar. Our previous study showed that around 40% frail PD patients had depressive symptoms, while depression was rare in PD patients without frailty [13]. More importantly, physical frailty and depressive symptoms had additive adverse effect on the nutritional status and clinical outcome [13].…”
Section: Introductionmentioning
confidence: 98%
“…However, most of the western studies focus on hemodialysis patients. A study in Korea [28] and in Hong Kong reported 75% and 43.2% [13] prevalence of depression respectively among the population undergoing CAPD. Such discrepancy could be explained by differences in in cohort size, characteristics of subjects, and the measurement tool for depression.…”
Section: Discussionmentioning
confidence: 99%
“…We used a validated Chinese questionnaire that consisted of 30 yes/no questions (Supplementary Figure 1) [6,13]. The questions involve assessment of subjective assessment of personal health, psychological state, physical state in terms of number of hospital or doctor visit and medication needs to be taken, body weight, need of assistance in different aspects of daily living and mobility.…”
Section: Assessment Of Frailtymentioning
confidence: 99%
See 1 more Smart Citation